Indicator-based estimates of the output gap in the euro area - Sebastian Weiske (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2018)
The output gap is a key variable of business cycle analysis and policy. Obtaining reliable estimates for it, is very difficult, though. Most real-time estimates are frequently revised over time. The idea of this paper is to use various indicators, for example from business surveys, that (i) were highly correlated with the output gap in the past and (ii) that are ideally not subject to revisions. According to a real-time analysis, indicator-based estimates prove to be more reliable than estimates from international institutions. Currently, estimates point to positive output gaps in the euro area.
Keywords: E32; E37; E6; 330; Business Cycles; Output Gap; Real-time Estimation; Business Survey Data